Some pennies are more equal than others: Inequitable school facilities investment in San Antonio, Texas - Marialena D. Rivera; Sonia Rey Lopez (Arizona State University, 2019)
In Texas, local taxpayers fund the majority of educational facilities construction and maintenance costs, with local wealth influencing facilities outcomes. The traditional school districts that comprise the predominantly Latino and segregated San Antonio area vary considerably in property wealth as well as district capacity and expertise. We conducted an analysis of 12 San Antonio area school districts to address the questions: 1) To what extent do state and local investments vary by district? 2) How do district actions and constraints affect facilities quality and equitable investment? Methods include descriptive quantitative analysis of facilities investment data and qualitative interviews with school district leaders, staff, and school finance experts. Examining Texas school finance data demonstrated the variance in school district investments in educational facilities. Despite some districts with lower property wealth exerting higher levels of tax effort, they were able to raise less money per student for educational facilities through interest and sinking taxes. Interview findings revealed that several districts acknowledge lacking the capacity to maintain high-quality facilities for all students. Respondents frequently criticized current state policies and funding for educational facilities as inadequate, inequitable, and inefficient and expressed a need for policy improvements in an era of increasing state disinvestment.